Losses Computation in Reciprocating Tubular Permanent Magnet Generator with SMC Core - Behrooz Rezaeealam (Institute of Advanced Engineering and Science, 2018)
Generally, the Permanent Magnet Tubular Generators (PMTG) are employed in the free-piston generator systems. In this paper, the PMTG with the core made of Soft Magnetic Composite (SMC) is employed, and then, the PMTG with the solid SMC core has cylindrical symmetry and also the outer diameter of the machine reduces in comparison to the ones with multipart laminated steel cores in which each part is radially placed along the air-gap and there is unexploited space between them. Here, a Finite Element Method (FEM) is developed in which the reciprocating motion of the translator is considered by moving mesh techniques and moreover, the Jiles-Atherton (JA) scalar hysteresis model is incorporated in the FE model to take into account the hysteresis losses. Then, the copper and core losses are computed and the equivalent circuit of the generator is derived. The calculated losses are compared with the ones obtained from the analytical methods.